Penentuan Karyawan Marketing Terbaik Menggunakan Metode WASPAS Dengan Pembobotan ROC - Inda Anggraini (JURNAL TEKNOLOGI INFORMASI, 2026)
This study aims to implement the Weighted Aggregated Sum Product Assessment (WASPAS) method in determining the best marketing employees using the Rank Order Centroid (ROC) method as a criteria weighting technique. Determining the best marketing employees is a decision-making problem that requires evaluation of various criteria, such as performance, communication skills, teamwork and others. This research method begins by collecting employee performance data based on criteria set by the Company. Next, the ROC method is used to determine the weight of each criterion, which is then applied in the WASPAS method calculation. The calculation steps include; data normalization, criteria weighting and final score calculation for each employee. The results of this study indicate that the WASPAS method with ROC weighting is able to produce objective employee rankings according to their performance in the field. Employees with the best performance get the highest score based on the calculations made. These results indicate that the implementation of the WASPAS method with ROC weighting can help the Company in determining the best marketing employees objectively and fairly. This method provides more informative and reliable decisions for decision-making related to human resources within the company. After calculations, the results showed that alternative data 23 (A23) Taufiq Alfarisyi was determined to be the best employee in the marketing department with a score of 0.915, ranking highest among the other alternatives.